2016
DOI: 10.1016/j.stemcr.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Decrease of the Histone Methyltransferase SUV39H1 in HSC Perturbs Heterochromatin and B Lymphoid Differentiation

Abstract: SummaryThe capacity of hematopoietic stem cells (HSC) to generate B lymphocytes declines with age, contributing to impaired immune function in the elderly. Here we show that the histone methyltransferase SUV39H1 plays an important role in human B lymphoid differentiation and that expression of SUV39H1 decreases with age in both human and mouse HSC, leading to a global reduction in H3K9 trimethylation and perturbed heterochromatin function. Further, we demonstrate that SUV39H1 is a target of microRNA miR-125b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 57 publications
3
88
0
Order By: Relevance
“…Recently, some noncoding RNAs have been demonstrated to play important roles in HSC functions, and their expression levels change with age. Djeghloul et al observed that the expression of micro-RNA miR-125b increased with age in human HSCs [95]. These authors also found that inhibition of miR-125 improved the capacity of HSCs from elderly individuals to generate B cells.…”
Section: Noncoding Rnasmentioning
confidence: 94%
“…Recently, some noncoding RNAs have been demonstrated to play important roles in HSC functions, and their expression levels change with age. Djeghloul et al observed that the expression of micro-RNA miR-125b increased with age in human HSCs [95]. These authors also found that inhibition of miR-125 improved the capacity of HSCs from elderly individuals to generate B cells.…”
Section: Noncoding Rnasmentioning
confidence: 94%
“…H3K9me3 is a histone modification critical for heterochromatin maintenance and has been shown to protect DNA from double strand breaks (107). Thus, the age-associated decline of this histone methyltransferase could also contribute to the accrual of DNA damage due to genome instability (108). It is likely that as more information about epigenetic regulation in HSCs is revealed, more connections between histone modifications and age-associated DNA damage accrual will also be established.…”
Section: Drivers Of Dna Damagementioning
confidence: 99%
“…We first assessed the spatial distribution of histone H3 lysine 9 trimethylation (H3K9me3), as a marker of constitutive heterochromatin (Becker et al, 2016) (Bannister et al, 2001). In freshly isolated HSCs, and in lymphoid progenitors, H3K9me3 was homogeneously distributed along the entire peripheral margin of the nucleus ( Figure 4A), as previously described (Djeghloul et al, 2016;Ugarte et al, 2015). By contrast, in freshly isolated myeloid progenitors, H3K9me3 distribution was more heterogeneous: foci were detected in the nucleoplasm, and at the peripheral margin of the nucleus, the density of H3K9me3 foci was lower in the invaginated regions than the other (convex) regions ( Figure 4A).…”
Section: Resultsmentioning
confidence: 97%